THE EFFECT OF USING COMPARE-DIAGNOSE-OPERATE (CDO) STRATEGY TOWARDS STUDENTS’ NARRATIVE TEXT WRITING SKILLS IN EIGHTH GRADE - Simanjuntak, Sarah Evelyn; Octavianna, Yessy; Lestari, Febrika Dwi (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The purpose of this study is to determine whether the Compare-Diagnose-Operate (CDO) technique can significantly impact grade 8 SMP N 8 Medan students' capacity to compose narrative texts. This kind of research employs experimental methodology. Pre- and post-tests are used independently in the design. This study compares the abilities of pupils using the CDO (Compare-Diagnose-Operate) technique before and after it was implemented. 24 pupils from the experimental class and 24 classes from the control class of class 8 at SMP N 8 Medan comprise the sample for this study. Data collection the method is administered through a written exam. The results of the study show how the CDO (Compare-Diagnose-Operate) method affects eighth-grade students' writing abilities when it comes to narrative texts. The study's conclusions show that grade 8 students' capacity to create narrative texts at SMP N 8 Medan is impacted by the CDO (Compare-Diagnose-Operate) technique.The higher up average score of pupils who used the CDO technique is evidence of this. based on the t-test data analysis. It is established that the control class has an average of 0.71 and the experimental class has an average of 0.81. The experimental class has a higher standard deviation value than the control class. It indicates that Ha accepted and Ho rejected. It indicates that instruction using the CDO (Compare-Diagnose-Operate) approach has a major impact on eighth grade students' capacity to compose narrative texts at SMP N 8 Medan.The CDO technique has a significant influence on how effectively students interact in writing clases when they are taught narrative texts, because using of the CDO strategy can increase student achievement in writingclass.